Treatment of vegetable oil refinery wastewater by sorption of oil and grease onto regranulated cork - A study in batch and continuous mode - Ariana M. A. Pintor (2015)
The feasibility of a novel sorption treatment using regranulated cork granules for oil and grease (O&G) removal from real vegetable oil refinery wastewaters (VORW) was investigated and compared to similar treatment of oil-in-water emulsions. O&G sorption from real VORW onto regranulated cork particles was studied at different pH and ionic strength conditions. Only wastewater acidification was able to effectively destabilize the O&G emulsion in the wastewater, enhancing the sorption process (efficiency over 80% at pH 2.0). A 3-factor, 3-level (3(3)) Box-Behnken experimental design was used to examine the effect of pH, ionic strength and soap/oil ratio on O&G removal efficiency in oil-in-water emulsions. All effects were significant (p < 0.05) when considered individually, but no significant interactions were observed. pH was found to have the strongest effect, supporting the initial observations in real VORW. The treatment of a simulated wastewater (60% soap/oil ratio, 0.2 M NaCl and pH 2.0) was completed in batch and continuous mode. Freundlich and linear partitioning models were used to describe 082G sorption equilibria. Continuous treatment was successfully carried out in a stirred-tank reactor using a cork dosage of 3.4 g L-1, a stirring speed of 250 rpm and a flowrate of 10 mL min(-1). The reactor was fed for 8 h with simulated wastewater (205 +/- 30 mg L-1 O&G) yielding an effluent with an O&G content below 15 mg L-1 (discharge limit defined in Portuguese legislation), A mass transfer model was applied to describe the O&G sorption kinetics in batch and continuous stirred-tank reactors.